International statistical review - International Statistical Institute (London: ISI, 1933)
Access available online from 1997-
Keywords: Statistics -- Periodicals; Statistics -- Bibliography -- Periodicals; Statistics -- Bibliography; Statistics -- Periodicals; ECONOMETRICS; MATHEMATICAL STATISTICS; STATISTICAL METHODOLOGY